Writing Ability of Second Grade Elementary School Students - Miftari Putri Destari; Febrina Dafit (Universitas Pendidikan Ganesha, 2022)
There are still many students who have not mastered writing skills well, especially in the lower grades. Writing problems that often occur in students in low grades are writing letters upside down, often exchanging certain letters, often leaving one letter or exaggerating one letter in the word written. The purpose of this study was to analyze writing skills and factors that influence students' writing abilities. This research belongs to the type of qualitative descriptive research with the research subjects namely five grade II elementary school students. Data collection in the study was carried out using observation, interview, and documentation methods with research instruments in the form of interview guidelines and observation guidelines. The data obtained in the study were then analyzed using data analysis techniques from Miles and Huberman. Namely consisting of Data Reduction, Data Presentation and the last is the Drawing of Conclusions/Verification stage. The results of the research analysis showed that most of the students mastered writing skills quite well, even though there were some components of writing skills that had not been well mastered by students, such as the aspect of spelling EYD correctly sometimes students made mistakes in the spelling. The factors that affect students' writing skills are the lack of students' ability to memorize letters, the attention of parents, and the teacher's way of teachi.